Resistance to Colletotrichum lindemuthianum in transgenic common bean expressing an Arabidopsis thaliana defensin gene - Espinosa-HuertaCruz, Elsa; Quintero-Jiménez Anareli; Sánchez-García Bertha María; Acosta-Gallegos, Jorge Alberto; Mora-Avilés María Alejandra (Revista Mexicana de Ciencias Agrícolas, 2018)
The defensin gene from Arabidopsis thaliana is an antimicrobial peptide that provides protection to a wide array of pathogens. Transgenic common bean (Phaseolus vulgaris L.) plants of cv. Flor de Mayo Anita constitutively expressing the defensin pdf1.2 gene were generated by Agrobacterium-mediated transformation via hypocotyls direct organogenic regeneration. The pdf1.2 gene under the control of promoter CaMV-35S was expressed in transformed common bean plants challenged with Colletotrichum lindemuthianum. The observed response was a significant reduction in the formation of lesions and spore mass proliferation in T0, T1 and T3 lines as compared to non-transformed plants. Twenty- seven T3 common bean transgenic plants from 5 independent lines expressing pdf1.2 gene showed resistance to C. lindemuthianum races 448 and 1472 compared to non-transformed plants. Analysis of the level of pdf1.2 gene expression by Q-PCR indicated that all plants considered resistant or tolerant had similar levels of transcriptional expression as opposed to susceptible plants, which did not have detectable levels of gene expression.